Penguatan Pengawasan Keimigrasian Terhadap Orang Asing di Wilayah Indonesia dalam Menjaga Keamanan dan Ketertiban Nasional Melalui TIMPORA - Febrianjes Tobing; Jhon Vito Azarya Munthe; Muhammad Akbar Meningkat Tumanggor (Jurnal Ilmiah Penegakan Hukum, 2026)
Immigration supervision of foreigners in Indonesia is a strategic aspect in maintaining security, national order, and state sovereignty amidst increasing global mobility. This study aims to analyze the strengthening of immigration supervision through the role of the Foreigner Supervision Team (TIMPORA) by identifying ongoing weaknesses, such as suboptimal supervision of the presence and activities of foreigners after entering Indonesian territory, limited human resources, weak inter-agency coordination, and the incomplete integration of the immigration information system. The research method used is normative juridical with a statutory and conceptual approach, by examining various regulations such as Law Number 6 of 2011 concerning Immigration and Regulation of the Minister of Law and Human Rights Number 50 of 2016 concerning the Foreigner Supervision Team. The results of the study indicate that immigration supervision has a strong legal basis, but its implementation has not been optimal. Therefore, strengthening is needed through optimizing integrated technology-based systems, improving inter-agency coordination through TIMPORA, and strengthening the capacity of immigration officials to create legal certainty, prevent immigration violations, and maintain national security stability.